The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1002/j.1460-2075.1985.tb03983.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo modulation of yeast tRNA gene expression by 5′-flanking sequences.

Abstract: A pentadecanucleotide sequence, TTTCAACAAATAAGT, contiguous with the 5′‐end of Saccharomyces cerevisiae tRNA‐Leu3 coding sequence acts as a positive modulator of transcription in a homologous in vitro system. To determine whether modulation also takes place in vivo, the amber suppressor forms of tRNA‐Leu3 genes with different 5′‐flanking sequences were generated by site‐specific mutagenesis and cloned into YCp19, a yeast vector maintained at 1‐2 copies per cell. These plasmids were transformed into S. cerevisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 37 publications
(19 reference statements)
1
51
0
Order By: Relevance
“…2B). Since the lys2-801am allele is efficiently suppressed by insertion of serine (Brandriss et al 1976), leucine (Raymond et al 1985), or tryptophan (Kim and Johnson 1988), the lack of suppression by tRNA His am suppressor variants indicates lack of charging of these tRNAs by other amino acids. Furthermore, the dramatically increased lys2-801am suppression upon overexpression of HTS1 indicates that histidine is inserted under these conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2B). Since the lys2-801am allele is efficiently suppressed by insertion of serine (Brandriss et al 1976), leucine (Raymond et al 1985), or tryptophan (Kim and Johnson 1988), the lack of suppression by tRNA His am suppressor variants indicates lack of charging of these tRNAs by other amino acids. Furthermore, the dramatically increased lys2-801am suppression upon overexpression of HTS1 indicates that histidine is inserted under these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, suppression almost certainly occurs by insertion of histidine, since the Kex2 serine protease requires histidine at the catalytic H213 position, and since suppression requires overexpression of HTS1. Furthermore, it is unlikely that either tRNA His am C 73 or tRNA His am A 73 is appreciably mischarged, since suppression of a lys2-801am mutation is almost undetectable, although this mutation is known to be suppressed by insertion of any of several different amino acids (Brandriss et al 1976;Raymond et al 1985;Kim and Johnson 1988), and since almost all the observed suppression requires overexpression of HTS1. Second, we showed that thg1-D cells are viable in spite of the lack of detectable G À1 in their tRNA His , but only if both tRNA His and HTS1 are overproduced.…”
Section: Resultsmentioning
confidence: 99%
“…TFIIIB appears not to recognize specific sequences, but to be directed to its 40 bp long DNA binding site, upstream of the transcriptional start site, by intragenically bound TFIIIC (11 We analyzed a large collection of S.cerevisiae tRNA genes to derive a conserved sequence element (CSE) in the neighborhood of the transcriptional start site (Fig. IA), as others have done previously (16)(17). The sequence at the start site ofthe tRNALeu3 gene conforms well with the CSE; the matching block TTTCAAC is located at positions -15 and -9 upstream of the mature coding sequence and includes the start site (the purine A at position -11) indicated by the arrow in Figure lB.…”
Section: Introductionmentioning
confidence: 99%
“…However, some 5' flanking substitutions do result in decreased promoter efficiency (19,20). Moreover, genes coding for a number of abundant yeast tRNAs (tRNALeu, tRNAArg, tRNALys, tRNAser) contain a conserved motif YYCAACAAATAAGT in their 5' flanks (21). Deletion of a DNA segment containing this element from tRNALeU and tRNATYr genes results in decreased transcription (22,5 (9).…”
Section: Introductionmentioning
confidence: 99%